The Impact of Social Media Influencers and Content Quality Unraveling the Mediating Role of Trust on Purchase Intention - Cipta Canggih Perdana; Carolina Novi Mustikarini; Erwin Parega (Program Pascasarjana STIE Amkop Makassar, 2023)
In the digital landscape today, social media platforms dominate as primary channels for sharing information, shaping culture, and fostering social interaction. This study investigates the interplay between Social Media Influencer Influence, Content Quality, mediated by Trust, in shaping consumer Purchase Intentions. Using a cross-sectional quantitative design, primary data was collected through structured online questionnaires distributed via Google Docs and shared on platforms like WhatsApp, Instagram, Twitter and Facebook. Convenience sampling included 110 active social media users following influencer accounts in Indonesia and globally. Partial Least Square (PLS) analysis, facilitated by SmartPLS software, explored the relationships between variables. Results highlight the significant impact of Social Media Influencer Influence (X1) on Purchase Intentions (Y) (H1) and Content Quality (X2) on Purchase Intentions (Y) (H2), underscoring their roles in shaping consumer purchase decisions. Additionally, Social Media Influencer Influence (X1) on Trust (Z) (H3) and Content Quality (X2) on Trust (Z) (H4) emphasize their contributions to building consumer trust. Notably, Trust (Z) substantially affects Purchase Intentions (Y) (H5), reaffirming its pivotal role in shaping consumer behavior. This study provides valuable perspectives on the dynamics of influencer marketing, underscoring the significance of both Content Quality and Trust in driving Purchase Intentions. It contributes to the marketing domain by enhancing comprehension of effective influencer marketing strategies and their impact on consumers Keywords: Social Media Influencer, Content Quality, Trust, Purchase Intention